Impact of Tulsi Ingredients on Gonadal Development of Common Carp, Cyprinus Carpio under Tarai Region of Uttarakhand - Sharma, Adita; Singh, I. J. (Indian Journal of Hill Farming, 2018)
The present study was conducted for comparing the effect of Tulsi ingredients, Eugenol and Ursolic acid on the gonadal of common carp (Cyprinus carpio) under Tarai condition of Uttarakhand. The results revealed that role of Ursolic acid in enhancing gonadal development and effect of Eugenol in decreasing gonadal development in C. carpio. Indicators of reproductive profile (GSI, fecundity and sperm count) exhibited more potency of Ursolic acid and less potency of Eugenol in gonadal differentiation and development. These observations indicate that Eugenol and Ursolic acid can also be used for selective enhancement of gonadal development depending upon the requirement.